A global trend toward law and order harshness?. Issue 4 (20th July 2015) - Wenzelburger, Georg
Abstract : A popular claim made by criminologists argues that globalization has created a general punitive turn in Western industrialized countries and led to much harsher law and order policies. The present paper challenges this view and adds to the literature in two respects as follows: first, it presents empirical evidence that substantial differences in law and order policies remain between Western industrialized countries even when law and order policy is measured in a much more finely grained manner than previously. Second, the paper provides empirical evidence for a persisting influence of the partisan ideology of governments and the party system characteristics of a country on its law and order policies: whereas the general trend of increasing economic globalization may well set the overall tone, this impact is conditioned by national political and institutional settings – and the ideology of the government as well as the party system in particular.